(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: The linguistic features of science fiction literature encompass various stylistic and thematic elements that differentiate it from other genres. This study explores the unique vocabulary, syntax, and narrative techniques that authors employ to construct futuristic worlds, advanced technologies, and complex characters. It examines the use of neologisms, allegory, metaphor, and dialogue that reflect societal concerns and human experiences in speculative contexts. Through a linguistic lens, this analysis seeks to uncover how language shapes the reader's understanding of science fiction, its ideological implications, and its impact on cultural narratives.